UPAYA MENINGKATKAN HASIL BELAJAR IPS TEMA LINGKUNGAN MELALUI PENGGUNAAN ALAT PERAGA BAGI SISWA KELAS I SD NEGERI 2 CISERO - N. Rita Sutresnawati; Nanih Sulastri; Nurjanah (CV Putra Publisher, 2023)
is because in the learning process the teacher does not use visual aids. Meanwhile, one of the objectives of the social studies subject is for students to get to know concepts related to people's lives and their environment. Based on that, a class action research was carried out with the aim of increasing student achievement in social studies about describing the location of the house using three-dimensional teaching aids. This research was conducted in class I SD Negeri 2 Cisero, Cisurupan District, Garut Regency. Academic Year 2018/2019. With a sample of 30 people through classroom action research. Data collection in this study was carried out through observation to observe students' activities in learning and tests to determine student social studies learning outcomes before and after learning. The results obtained in this study can be concluded that before using the three-dimensional teaching aids students who reach the passing grades pass a few and have a low average score. After using three-dimensional teaching aids, student learning outcomes increase and student participation in learning also becomes better. With three-dimensional teaching aids reduce verbalism in students